2013
DOI: 10.1186/1751-0147-55-68
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the spleen, liver, gallbladder, caudal vena cava and portal vein in healthy calves from birth to 104 days of age

Abstract: BackgroundMany of the ultrasonographic abdominal findings of adult cattle probably also apply to calves. However, significant changes associated with ruminal growth and transition from a milk to a roughage diet occur in young calves during the first few months, and it can be expected that ultrasonographic features of organs adjacent to the rumen such as spleen and liver also undergo significant changes. These have not been investigated to date and therefore the goal of this study was to describe ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 19 publications
4
12
0
5
Order By: Relevance
“…In a serial study of calf abdominal organs from birth to 104 days of age, the pattern of splenic parenchyma did not change. 12 As the study involving calves used a 5-MHz lowfrequency transducer, the resolution was not high enough to distinguish the changes in the splenic parenchyma. In addition, a previous study of 27 dogs reported that the splenic substance has a uniformly mottled echogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In a serial study of calf abdominal organs from birth to 104 days of age, the pattern of splenic parenchyma did not change. 12 As the study involving calves used a 5-MHz lowfrequency transducer, the resolution was not high enough to distinguish the changes in the splenic parenchyma. In addition, a previous study of 27 dogs reported that the splenic substance has a uniformly mottled echogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The reticulum, rumen, spleen, liver, kidney, omasum, abomasum, intestine, and peritoneum were examined for any alteration in their normal structure and movement. The dimensions of the liver, portal vein (PV), and caudal vena cava (CVC) were measured as described previously [ 13 , 19 ], while the spleen was examined as previously described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…18). 9,10 Branches of the portal vein and the hepatic veins in the parenchyma increase in size toward the portal vein and caudal vena cava, respectively. The wall of the portal vein is generally better defined than that of the hepatic veins because of an echoic rim, but clear differentiation is only possible in the area where stellar ramifications of the portal vein branch into the parenchyma.…”
Section: Ultrasonographic Findings Of the Liver And Gallbladdermentioning
confidence: 99%
“…22). 9,10 The wall is more echogenic than the wall of the caudal vena cava, and the portal vein is seen at more ICSs than the caudal vena cava because of a more ventral position and less superimposition of the lungs. It is always seen at the 7th to 11th…”
Section: Ultrasonographic Findings Of the Liver And Gallbladdermentioning
confidence: 99%